A ANALYSIS OF THE EFFECT OF INVESTMENT AND CAPITAL EXPENDITURE ON POVERTY IN SOUTH SULAWESI PROVINCE WITH ECONOMIC GROWTH AS INTERVENING VARIABLE: ANALYSIS OF THE EFFECT OF INVESTMENT AND CAPITAL EXPENDITURE ON POVERTY IN SOUTH SULAWESI PROVINCE WITH ECONOMIC GROWTH AS INTERVENING VARIABLE - Aqidah, Suci (ICOR: Journal of Regional Economics, 2022)
One of the keys to success in development is reducing the number of poor people. Efficiency in reducing the number of poor people is a big growth for policy options and development tools. Development is the goal of developing countries as they progress. The success of development is one indicator of economic development, through the hope of increasing economic numbers so as reduce poverty. This is done to see what things affect poverty through economic growth. This study uses path analysis, the results of statistical tests show that the direct influence of investment variables (X1) has a positive and insignificant effect on economic growth (Y1), capital expenditures (X2) has a positive and significant effect on economic growth (Y1), investment (X1) has a negative and significant effect on poverty (Y2), capital expenditure (X2) has a negative and significant effect on poverty (Y2), economic growth (Y1) has a positive and insignificant effect on poverty (Y2). While the inderect effect of the investment variable (X1) has a significant effect on poverty (Y2) through economic growth (Y1) and capital expenditure (X2) has a significant effect on poverty (Y2) through economic growth (Y1). Keywords: Poverty, economic growth, investment and capital expenditure